PENGEMBANGAN SISTEM INFORMASI ADMINISTRASI ASISTEN MATA KULIAH PRAKTIKUM DAN RESPONSI DI JURUSAN ILMU KOMPUTER UNIVERSITAS LAMPUNG - Nova Ayu Lestari Siahaan; Akmal Junaidi; Favorisen Rosyking Lumbanraja; Bambang Hermanto (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
The processing system of the administrative information for lab works and problem exercises of the student at the Department of Computer Science, Universitas Lampung, is still carried out conventionally. In this manner, the data is physically stored in the form of recorded documents and leave them on the shelf. Sometimes, data collection in this form can be lost and require a longer time to manage. For this reason, a lab assistant’s information system is developed by the waterfall approach that runs on a web-based platform. The system can provide data and generate information about lab assistants and participants faster and more accurately. It is implemented using the framework Laravel and Black Box testing as a functional test of the system. The testing indicates that the system functions work to the software requirement specification.